Evaluation of rational energy costs for liquid dispersion in piston compressors with a two-phase working fluid - V. E. Scherba; A. K. Kuzhbanov; M. I. Gildebrandt; V. Yu. Kudentsov; N. S. Galdin; A. A. Gladenko (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper considers the condition of efficient operation of a piston compressor with coolant injection, which consists in the fact that the costs of its spraying and injection should be less than the gain in indicator work obtained with intensive gas cooling and the compression process approaching isothermal. The maximum relative gain in the supplied technical work is no more than 25 % when using a coolant injection system. Therefore, to obtain an energy effect from using a cooling system, the costs of organizing it should not exceed (10–15) %. The greatest influence on the amount of energy gain when organizing liquid injection is exerted by the average radius of coolant droplets, then by the relative amount of injected liquid. The efficiency of liquid injection increases with an increase in the ratio of the discharge pressure to the suction pressure and with a decrease in the number of crankshaft revolutions.